Effects of mindfulness-based cognitive therapy on older adults with sleep disorders: a systematic review and meta-analysis - González-Martín, Ana María; Aibar-Almazán, Agustín; Rivas-Campo, Yulieth; Marín-Gutiérrez, Alejandro; Castellote-Caballero, Yolanda (Frontiers in Public Health, 2023)
Objective This systematic review and meta-analysis was conducted to analyze the effectiveness of a mindfulness-based program on sleep quality in healthy non-institutionalized older people. Methods This study was conducted following the PRISMA (Preferred Reporting Items For Systematic Reviews And Meta-Analyses) guidelines. The search was conducted during May and June 2023 using four databases: Pubmed, Scopus, Web of Science, and CINAHL. Different keywords combined with Boolean operators were used. Only 10 articles of the initial 177 were included. In the study, the standardized mean difference (SMD) was used along with a 95% confidence interval to measure the effect. Heterogeneity among the studies, assessed using Cochran's Q-test and the I2 statistic was found to be low, leading to the use of a fixed-effects model in the analysis. The effect size was expressed as Hedge'g. Furthermore, a subgroup analysis was conducted, taking into account the various tools used to assess sleep conditions. Results Mindfulness was found to reduce poor sleep quality in people with both long-term and short-term sleep disorders. Weighting effect model Hedge'g = −0.344 with a 95% confidence interval ranging from −0.425 to −0.263. In all cases, statistically significant results were observed, as well as moderate and negative effect sizes according to the Hedge's g index: −0.326 for Insomnia Severity Index (ISI), −0.343 for Pittsburgh Sleep Quality Index (PSQI), and −0.28 for Sleep Onset Latency (SOL). Conclusion This systematic review and meta-analysis found that mindfulness can be used to remedy poor sleep quality in older people, so it could be a viable treatment option for insomnia or other problems related to poor sleep quality in this population.